Fivefold enhancement in stability of organic light-emitting diodes with addition of non-evaporable getter pumps. (8th June 2017) - Le, Duy C.; Oyama, Shiho; Sakai, Heisuke; Porcelli, Tommaso; Siviero, Fabrizio; Maccallini, Enrico; Urbano, Marco; Murata, Hideyuki
Abstract: We demonstrate a significant enhancement of the operational stability of organic light-emitting diodes (OLEDs) by fabricating the devices under ultrahigh-vacuum (UHV) conditions in the region of 10 −10 –10 −11 Torr. The UHV condition is achieved by utilizing non-evaporable getter pumps together with regular turbo molecular pumps in an OLED deposition chamber. The short-term stability of the OLEDs is prolonged fivefold because of the removal of detrimental gases, especially water. We suggest that ultra-clean fabrication conditions are indispensable for revealing the true intrinsic degradation mode of OLEDs. Additionally, we analyze the effect of operating residual gas analyzers during the device fabrication.